Vinyl ruthenium-modified biphenyl and 2,2'-bipyridines - Scheerer, Stefan; Rotthowe, Nils; Abdel-Rahman, Obadah S; He, Xiaoyan; Rigaut, Stéphane; Kvapilová, Hana; Záliš, Stanislav; Winter, Rainer F (Inorganic chemistry, 2015)
We report here on ruthenium alkenyl complexes 2 and 3 derived from 2,2'-bipyridine and their Re(CO)3X adducts 4a,b and 5. Detailed electrochemical studies on these complexes and spectroscopic characterization of their oxidized forms by IR, UV/vis/NIR, and electron paramagnetic resonance spectroscopies as well as quantum chemical studies reveal sizable (bridging) ligand contributions to the redox orbitals. Engagement of the free bipy functions of complexes 2 and 3 in binding to the electron-withdrawing fac-Re(CO)3X (X = Br, Cl) moiety enhances the metal-to-ligand charge-transfer character of the optical excitations, causes sizable anodic shifts of the redox potentials, and decreases the number of observable anodic redox waves by one when compared to complexes 2 and 3. Despite the decreasing electron density at the terminal or bridging alkenyl bipyridine ligand, the anodic redox processes still maintain appreciable ligand character as is seen by the shifts of the Ru(CO) and Re(CO)3 stretching frequencies on oxidation. Binding of the fac-Re(CO)3X moiety also attenuates the degree of ground-state delocalization in the mixed-valent states.